Assessment of organophosphate pesticides in soils and vegetables from agricultural areas of Delta Central District, Nigeria - Godswill Okeoghene Tesi; Kingsley Ezechukwu Okpara; Juliet Ngozi Tesi; Iwekumo Ebibofe Agbozu; Kuaanan Techato (Scientific Reports)
Abstract The application of agrochemicals such as organophosphate pesticides (OPPs) has several benefits in agriculture but also poses great risks to the environment and human well-being. Thus, this study was conducted to determine the concentrations, distribution pattern, relationships, potential risks and sources of OPPs in agricultural soils and vegetables from Delta Central District (DCD) of Nigeria to provide useful information for pollution history, establishment of pollution control measures and risk management. Fourteen OPPs were determined in the soil and vegetables using a gas chromatograph-mass selective detector (GC-MSD). The ∑14 OPPs concentrations varied from 5.29 to 419 ng g−1 for soil and 0.69 to 130 ng g−1 for vegetables. On average, pirimiphos methyl (23.8 ng g−1) and diazinone (4.74 ng g−1) were the dominant OPPs in soils and vegetables respectively. The cumulative ecological risk assessed using the toxicity-exposure-ratio (TER) and risk quotient (RQ) approaches revealed that there was a high risk of OPPs to soil organisms. The increasing order of OPPs toxicity to the soil organisms was chlorpyriphos < fenitrothion < diazinone < pirimiphos methyl while the cumulative human health risk suggested there was adverse non-carcinogenic risk for children but not for adults exposed to OPPs in these agricultural soils and vegetables.